Biomechanical Quantification of Mendelsohn Maneuver and Effortful Swallowing on Pharyngoesophageal Function. (13th June 2017) - Doeltgen, Sebastian Heinrich; Ong, Ellisa; Scholten, Ingrid; Cock, Charles; Omari, Taher
Abstract : Objective: To quantify the effects of 2 swallowing maneuvers used in dysphagia rehabilitation—the Mendelsohn maneuver and effortful swallowing—on pharyngoesophageal function with novel, objective pressure‐flow analysis. Study Design: Evaluation of intervention effects in a healthy control cohort. Setting: A pharyngoesophageal motility research laboratory in a tertiary education facility. Subjects: Twelve young healthy subjects (9 women, 28.6 ± 7.9 years) from the general public, without swallowing impairment, volunteered to participate in this study. Methods: Surface electromyography from the floor‐of‐mouth musculature and high‐resolution impedance manometry–based pressure flow analysis were used to assess floor‐of‐mouth activation and pharyngoesophageal motility, respectively. Subjects each performed 10 noneffortful control swallows, Mendelsohn maneuver swallows, and effortful swallows, with a 5‐mL viscous bolus. Repeated measures analyses of variance was used to compare outcome measures across conditions. Results: Effortful and Mendelsohn swallows generated greater floor‐of‐mouth contraction ( P =. 001) and pharyngeal pressure ( P <. 0001) when compared with control swallows. There were no changes at the level of the upper esophageal sphincter, except for a faster opening to maximal diameter during maneuver swallows ( P =. 01). The proximal esophageal contractile integral was reduced during Mendelsohn swallows ( P =. 001). Conclusion: Effortful and Mendelsohn maneuver swallows significantly alter the pharyngoesophageal pressure profile. Faster opening of the upper esophageal sphincter may facilitate bolus transfer during maneuver swallows; however, reduced proximal esophageal contractility during Mendelsohn maneuver swallows may impair bolus flow and aggravate dysphagic symptoms.